COMPARING STRESS LEVELS AMONG MEDICAL EMERGENCY UNIT WORKERS IN TEACHING HOSPITALS ACROSS LAHORE: A QUANTITATIVE ANALYSIS OF PRECISION - Fizzah Ali,; Fatima Suhaib,; Hajra Talat,; Malik Zain Ul Abideen,; Uzair Abu Bakar,; Maria Javaid, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Stress is characterized as a condition of anxiety or tension spurred on by challenging circumstances. Stress is a normal human reaction that motivates us to deal with obstacles and dangers in our lives. The study aimed to investigate the levels of stress that employees in the medical emergency unit (MEU) industry face and any possible relationship between work satisfaction, and perceived stress. The objective of the study was to assess and compare the stress levels of MEU workers in different teaching hospitals in Lahore using the PSS-10 stress scale. Our research aims to examine and compare the perceived stress based on gender, profession, and marital status. Methods: The study employed a quantitative cross-sectional design to assess and compare stress levels among MEU workers in teaching hospitals across Lahore. The target population consisted of MEU workers in teaching hospitals across Lahore. The perceived stress levels were measured using the PSS-10 (Perceived Stress Scale) questionnaire, a widely accepted, validated, and reliable instrument for assessing stress perception in individuals. The data was subjected to both descriptive and inferential statistical analyses using the SPSS. Descriptive statistics, including means and standard deviations, were employed to summarize stress levels among medical emergency unit workers in different teaching hospitals. Independent t-tests and ANOVA were utilized to compare stress levels across teaching hospitals. Results: In this study involving 304 medical professionals, participants, on average, were 29.95 years old with a mean stress score of 20.99. The majority were female (62.8%), married (50.7%), and affiliated with Mayo Hospital (17.4%). Occupation-wise, 66.45% were doctors, and no significant difference in perceived stress was observed among professional categories. However, there was a significant difference in stress scores among hospitals, with FMH participants exhibiting lower stress compared to others (p<0.005). Conclusion: The study found significant differences in stress among medical emergency unit staff in teaching hospitals in Lahore. The results highlight the significance of targeted interventions and support initiatives to improve worker resilience and well-being in high-stress healthcare settings. It provides valuable information for improving stress management and preventive tactics.